Effect of saturation on mechanical behavior of cement mortar based on 8-type tensile test. Issue 2 (May 2019) - Gu, C; Xu, J Y; Meng, B X
Abstract: Based on the purpose of revealing the effect of saturation on static tensile mechanical behaviour of cement mortar, the single-axis static tensile test was carried out for 8-type cement mortar specimens with the saturation of 0%, 50%, and100% respectively. The WDW-20 microcomputer controlled electronic universal testing machine was used in this paper. The date obtained from test indicates that the stress-strain curves of different saturation cement mortar are similar, stress with strain increases, the stress growth rate increases gradually. With the increase of saturation, the static tensile strength of cement mortar gradually decreases, and the stiffness of cement mortar gradually decreases, and the deformation performance gradually improves, and the maximum tensile strain increases gradually. Compared with dry cement mortar specimens, the tensile strength of saturated cement mortar specimens is decreased by 23.36%; the maximum tensile strain of semi-saturated and saturated cement mortar specimens is increased by 4.79% and 23.43% respectively. The elastic modulus of the dry and the semi-saturated cement mortar specimens are similar, when they are under pulled, and are larger than the elastic modulus of saturation cement mortar specimens.